Hepato-Genoprotective Activities of Methanol Extract of The Stem Bark of Adansonia Digitata LINN. In Wistar Rats Challenged with Sodium Arsenite (Nigerian Journal of Physiological Sciences, 2020)
Arsenic exposure is an issue of concern in developing countries, consequently leading to arsenicosis which has been implicated in the development of cancers. The stem bark of Adansonia digitata (SBAD) has many traditional medicinal uses. The aim of the present study was to assess the antigenotoxic and hepatoprotective effects of methanol extract of SBAD (MESBAD) against sodium arsenite - induced toxicities in Wistar rats. These were assessed using the micronucleus induction assay and liver function tests with histology respectively. Thirty (30) rats distributed into six groups of five animals each were used for the experiment. Negative control (distilled water and rat pellets only), positive control [2.5 mg/kg body weight of sodium arsenite (SA)]. Test animals were challenged with SA and treated with 300 or 400 mg/kg body weight of MESBAD. The phytochemical analysis was also carried out according to standard procedures. The SA significantly (p